2019
DOI: 10.1111/birt.12465
|View full text |Cite
|
Sign up to set email alerts
|

Maternal comorbidity index and severe maternal morbidity during delivery hospitalizations in Texas, 2011‐2014

Abstract: Background Severe maternal morbidity (SMM) prevalence was 194.0 per 10 000 deliveries in Texas in 2015. Chronic, behavioral, and pregnancy‐induced conditions, as captured by a maternal comorbidity index, increase the risk for delivery‐related morbidity and mortality. The objective of the study was to examine the association between maternal comorbidity index and SMM among delivery hospitalizations in Texas. Methods Delivery‐related hospitalizations among Texan women aged 15‐49 years were identified using the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Adjusting for clinical comorbidities in our study reduced the relative Black–white disparity in SMM; however, substantial Black–white disparities in SMM remain in fully adjusted models. This finding aligns with previous studies that have found that clinical comorbidities alone may not be sufficient in predicting adverse maternal outcomes 21 . This suggests that continued efforts to better measure and evaluate other social determinants of health, and to eradicate harmful aspects of US maternity care such as structural racism, inequitable access to the health care systems, and implicit biases during clinical encounters are critical for ensuring health equity across racial/ethnic groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Adjusting for clinical comorbidities in our study reduced the relative Black–white disparity in SMM; however, substantial Black–white disparities in SMM remain in fully adjusted models. This finding aligns with previous studies that have found that clinical comorbidities alone may not be sufficient in predicting adverse maternal outcomes 21 . This suggests that continued efforts to better measure and evaluate other social determinants of health, and to eradicate harmful aspects of US maternity care such as structural racism, inequitable access to the health care systems, and implicit biases during clinical encounters are critical for ensuring health equity across racial/ethnic groups.…”
Section: Discussionsupporting
confidence: 87%
“…This finding aligns with previous studies that have found that clinical comorbidities alone may not be sufficient in predicting adverse maternal outcomes. 21 This suggests that continued efforts to better measure and evaluate other social determinants of health, and to eradicate harmful aspects of US maternity care such as structural racism, inequitable access to the health care systems, and implicit biases during clinical encounters are critical for ensuring health equity across racial/ethnic groups. In our study, claims data were linked to the birth certificate to make use of other important measures such as socioeconomic factors (e.g., marital status, education and WIC participation) and previous gynecological and obstetrical history (e.g., parity).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a number of risk factors for SMM and mortality have been identified, including maternal age, cesarean delivery, multifetal gestation, obesity, and preexisting chronic conditions . There is also evidence that additional factors, including obstetric and medical factors, unmarried status, low maternal education, and rural residency, may potentially increase the risk of SMM and pregnancy-related mortality . Although these clinical and sociodemographic factors are critical in understanding the maternal health crisis, it is equally important to investigate factors associated with availability, quality, and accessibility of maternity care resources .…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 There is also evidence that additional factors, including obstetric and medical factors, unmarried status, low maternal education, and rural residency, may potentially increase the risk of SMM and pregnancy-related mortality. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Although these clinical and sociodemographic factors are critical in understanding the maternal health crisis, it is equally important to investigate factors associated with availability, quality, and accessibility of maternity care resources. 26 These health care access factors will help to address spatial disparities and resource allocation in maternal care access in a particular region.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a relative paucity of evidence specifically describing the scope, extent, and patterns of SMM in the US South. With only a few exceptions [20][21][22] there is sparse evidence describing the epidemiologic patterns and population burden of SMM in the very states where both overall burden and racial and ethnic disparities are historically largest. For example, the pregnancy-related mortality ratio in Georgia from 2015 to 2017 was 25.1 per 100,000 live births, 23 among the highest rates in the United States.…”
mentioning
confidence: 99%